2018
DOI: 10.1038/s41591-018-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Mutant KRAS-driven cancers depend on PTPN11/SHP2 phosphatase

Abstract: The ubiquitously expressed non-receptor protein tyrosine phosphatase SHP2, encoded by PTPN11, is involved in signal transduction downstream of multiple growth factor, cytokine and integrin receptors. Its requirement for complete RAS-MAPK activation and its role as a negative regulator of JAK-STAT signaling have established SHP2 as an essential player in oncogenic signaling pathways. Recently, a novel potent allosteric SHP2 inhibitor was presented as a viable therapeutic option for receptor tyrosine kinase-driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
207
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(246 citation statements)
references
References 53 publications
10
207
0
Order By: Relevance
“…The GO term analysis also indicated that protein tyrosine kinase activity, transmembrane RTK activity, phosphatidylinositol-4,5-bisphosphate 3-kinase activity, as well as binding and activity of PI3K were related to human inguinal hernia diseases. Additionally, others also show that inguinal hernia-related essential proteins, PTPN11, CDC42, and SOS1 regulate the RAS/MAPK signaling pathway, which is another downstream effector of RTKs [51][52][53][54]. Furthermore, essential proteins, PIK3R1 and TGFBR1 are involved in the regulation of both the PI3K/AKT and RAS/MAPK signaling pathways [55][56][57].…”
Section: Discussionmentioning
confidence: 98%
“…The GO term analysis also indicated that protein tyrosine kinase activity, transmembrane RTK activity, phosphatidylinositol-4,5-bisphosphate 3-kinase activity, as well as binding and activity of PI3K were related to human inguinal hernia diseases. Additionally, others also show that inguinal hernia-related essential proteins, PTPN11, CDC42, and SOS1 regulate the RAS/MAPK signaling pathway, which is another downstream effector of RTKs [51][52][53][54]. Furthermore, essential proteins, PIK3R1 and TGFBR1 are involved in the regulation of both the PI3K/AKT and RAS/MAPK signaling pathways [55][56][57].…”
Section: Discussionmentioning
confidence: 98%
“…SHP2 is one of the promoters involved in RAS activation. SHP2 is a necessary mediator of resistance upon receiving MEK blockade therapy, reported in pancreatic and lung cancers (Ruess et al, ) (Figure A). Adaptive resistance of cancer cells to MEK blockade therapy also occurs due to feedback RTK activation (Misale et al, ).…”
Section: Mapk In Cancer Growth and Drug Resistancementioning
confidence: 93%
“…Activation of MEK (via phosphorylation) is induced by RAF isoforms, and its downstream target is ERK (Lu et al, ; Hazar‐Rethinam et al, ). Trametinib (Ablain et al, ), selumetinib (Ruess et al, ), and SL‐327 (Yan et al, ) are MEK inhibitors. Sensitivity to MEK inhibitors often occurs when there are mutations in upstream kinases.…”
Section: Mapk Signalingmentioning
confidence: 99%
“…These combination regimens have shown promising activity in preclinical models and are currently being evaluated in different clinical trials [63]. More recently, 3 studies provided compelling evidence suggesting that SHP2 inhibitors can overcome the adaptive response of KRAS -altered cancer cells to MEK inhibition [64,65,66]. These data pave the way for the clinical evaluation of combinations consisting of inhibitors of MEK and SHP2 for the treatment of KRAS -driven malignancies.…”
Section: Targeting Oncogenic Krasmentioning
confidence: 99%
“…First, more than 90% of PDAC cases are driven by oncogenic mutations affecting KRAS . While direct targeting of oncogenically mutated KRAS is still in its infancy [54,55], several approaches to indirectly target oncogenic KRAS, including combined CHK1/MAPKAP-K2 inhibition, CHK1 inhibition in combination with genotoxic chemotherapy, combined MEK/PI3K or combined MEK/SHP2 inhibition, have recently emerged and await clinical validation [60,61,62,64,65,66,68,71]. Second, a sizable fraction of PDAC cases harbor germline mutations in a number of DNA repair genes, particularly those involved in DSB repair [13,14,15,16,17,18,19,20,21,22,23].…”
Section: Clinical Perspectivementioning
confidence: 99%